FIXED POINT RESULTS FOR WEAK S-CONTRACTIONS VIA C-CLASS FUNCTIONS - Paunović, Ljiljana; Sezen, Müzeyyen Sangurlu; Ansari, Arslan Hojat (Bulletin of Natural Sciences Research, 2019)
In this paper, we prove some fixed point results for weak S-contraction mappings in partially ordered 2-metric spaces via C-class function. Our results are different and more general to the usual methods in the literature.